Stand-alone anterior lumbar interbody fusion - complications and perioperative results - Rodrigo Amaral; Ronaldo Ferreira; Luis Marchi; Rubens Jensen; Joes Nogueira-Neto; Luiz Pimenta (Revista Brasileira de Ortopedia)
ABSTRACT Objectives: Historically, anterior lumbar interbody fusion (ALIF) was related to high rates of intraoperative complications and adverse events related to interbody devices. In recent decades, there have been technical adjustments, and cages that are more suitable have emerged. The aim of this study is to evaluate the efficacy and complication rate of the use of stand-alone mini-ALIF using a self-locking cage., Methods: Retrospective single center study. Inclusion criteria: retroperitoneal mini-ALIF for single-level fusion (L5S1); self-locking cage; DDD/stenosis and grade I, spondylolisthesis. Exclusion criteria: posterior supplementation, previous fusion/arthroplasty. Endpoints: surgery data, intraoperative and perioperative adverse events related both to surgical access and to the intersomatic device., Results: Eighty-seven cases were enrolled. Median surgical time was 90 min; median blood loss was 100 mL. The median length of stay in the ICU was zero days; median hospital stay was one day. Ten cases had an adverse event (11.5%): four major adverse events (4.6%; 3 L bleeding; DVT; retroperitoneal haematoma; incisional hernia), and seven minor events (8%; peritoneum injury; minor vascular injury; events related to the cage). No cases of retrograde ejaculation were observed. There was improvement in pain, physical restriction, and quality of life (, p< 0.001). Conclusions: The mini-ALIF procedure performed for single-level fusion at the distal lumbar level demonstrated low adverse event rates related to both the surgical approach and to the intersomatic device, with reduced hospital stay and satisfactory perioperative clinical results.